Fingerprint pattern recognition from bifurcations: An alternative approach - Castañeda-Miranda, A.; Castañeda-Miranda, R.; Castano, Victor (Journal of Advanced Computer Science & Technology, 2015)
A pc-based automatic system for fingerprints recording and classification is described, based on the vector analysis of bifurcations. The system consists of a six-step process: a) acquisition, b) preprocessing, c) fragmentation, d) representation, e) description, and f) recognition. Details of each stage, along with actual examples of fingerprints recognition are provided.